Converting words : Maya in the age of the cross - Hanks, William F. (Anthropology of Christianity, 2010)
This pathbreaking synthesis of history, anthropology, and linguistics gives an unprecedented view of the first two hundred years of the Spanish colonization of the Yucatec Maya. Drawing on an extraordinary range and depth of sources, William F. Hanks documents for the first time the crucial role played by language in cultural conquest: how colonial Mayan emerged in the age of the cross, how it was taken up by native writers to become the language of indigenous literature, and how it ultimately became the language of rebellion against the system that produced it. Converting Words includes origi.